US trade policy and the US dollar - Makram Khalil; Felix Strobel (Deutsche Bundesbank, 2021)
We investigate the extent to which the effect of the 2018/2019 US import tariff hikes on US (post-tariff) import prices was offset by the concurrent appreciation of the US dollar and trace the source of the appreciation back to US trade policy itself. The dollar response to trade policy uncertainty (TPU) is key to assessing the overall impact of trade policies. Within a SVAR framework, identified TPU shocks account for a sizable fraction of the USD appreciation - against a broad currency basket, but also against the Chinese yuan. To rationalize the SVAR evidence, we build an open economy NK model featuring financial frictions, which accounts for uncertainty regarding future trade policy. In the model, an increase in TPU raises the relative demand for safer US assets, triggering an appreciation of the US dollar. Moreover, in assessing the offsetting effects from the exchange rate,we use detailed product data on unit values of manufacturing imports and document that Chinese exporters react to an USD appreciation by markedly lowering their US dollar-denominated export prices. This holds in particular for intermediate goods producers, which had been the main target of US trade policy in 2018 and 2019. Overall, we find that offsetting effects on the newly imposed tariffs were substantial.
Keywords: F31; F13; F14; F41; E31; 330; Trade policy uncertainty; safe-asset currency; two-country model with financial frictions; exchange rate pass-through to import prices; tariffs